2019
DOI: 10.1101/636910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid adaptation to Elevated Extracellular Potassium in the Pyloric Circuit of the Crab, Cancer borealis

Abstract: AbstractElevated [K+] is often used to alter excitability in neurons and networks by shifting the potassium equilibrium potential (EK) and, consequently, the resting membrane potential. We studied the effects of increased extracellular [K+] on the well-described pyloric circuit of the crab, Cancer borealis. A 2.5-fold increase in extracellular [K+] (2.5x[K+ Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 81 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…We observed that high pH (>9.5) did not silence the preparation, but silent states were observed in low pH (<6.5), consistent with previously published manual annotation of this data (Haley et al, 2018). Silent states were also observed in 2.5 × [ K + ], as reported earlier by He et al (2020). Previous work has shown that the isolated pacemaker kernel (AB and PD neurons) has a stereotyped trajectory from bursting through tonic spiking to silence when subjected to temperature and high [ K + ] perturbations (Ratliff et al, 2021).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…We observed that high pH (>9.5) did not silence the preparation, but silent states were observed in low pH (<6.5), consistent with previously published manual annotation of this data (Haley et al, 2018). Silent states were also observed in 2.5 × [ K + ], as reported earlier by He et al (2020). Previous work has shown that the isolated pacemaker kernel (AB and PD neurons) has a stereotyped trajectory from bursting through tonic spiking to silence when subjected to temperature and high [ K + ] perturbations (Ratliff et al, 2021).…”
Section: Resultssupporting
confidence: 78%
“…What remains unclear is if extreme perturbations of different modalities share common pathways of destabilizing and disrupting the pyloric rhythm (Ratliff et al, 2021). In principle, these environmental perturbations can disrupt neuron and circuit function in qualitatively different ways: e.g., changes in extracellular potassium concentration can alter the reversal potential of potassium (He et al, 2020) vs. changes in temperature can have varied effects on the timescales and conductances of all ion channels (Tang et al, 2010; Caplan et al, 2014). Because prior work was focussed on studying the limits of robustness, and lacked a detailed quantitative description of irregular behavior, the fine structure of the transition between functional dynamics and silent or “crashed” states remain poorly characterized (Ratliff et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crustacean stomatogastric ganglion (STG) is an excellent model system in which to study underlying network dynamics and mechanisms of circuit robustness both through recording from well-studied identified neurons and computational models of those neurons 33,[35][36][37][38] . Importantly, the physiological behavior of each neuron within the STG is relatively stereotyped, allowing us to determine whether a given pattern of activity is normal.…”
Section: Introductionmentioning
confidence: 99%